FAKTOR YANG MEMPENGARUHI KEPUTUSAN PENGAMBILAN KREDIT ANGGOTA KUD KUSUMA BAKTI DESA SIALANG KUBANG - Hamidin, Hamidin; Indrawati, Henny; Caska, Caska (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2019)
Abstract: This study aims to determine the factors that influence credit decision making for members of the Kusuma Bakti KUD Sialang Kubang Village. This research was conducted in the village of Sialang Kubang which is located in Perhentian Raja District, Kampar Kiri Regency. With a sample of 154 members using the Slovin formula. The research instrument used was a questionnaire using descriptive data analysis and multiple regression with the help of SPSS Version 20 software. Descriptive analysis results show the quality of service, credit procedures included in the good category, while the perception of high interest rates included in the very good category. Multiple linear regression analysis found that service quality, credit procedures, and perceptions of interest rates had a positive effect on credit decision making with a contribution of 63.6%. The results found a positive influence between service quality on credit decision making by 0.340 and there was a positive relationship between credit procedures on credit decision making by 0.252 and there was a positive influence between perceptions of interest rates on credit decision making by 0.545. The variable that has a greater influence on credit decision making is the interest rate perspective. The recommendations in this study are so that the number of members taking credit can be increased. There are several ways needed to improve member credit collection, namely by improving the quality of service and lowering interest rates, and credit procedures should not be too complicated so as to facilitate customers in conducting credit loan activities.Key Words: Service Quality, Credit Procedures, Perception Of Interest Rates, Credit Decision Making